Biotechnology of Microalgae, Based on Molecular Biology and Biochemistry of Eukaryotic Algae and Cyanobacteria - Takashi Osanai (Frontiers Research Topics, 2017)
Bioechnology of microalgae takes much attention because of their ability to utilize light energy and fix CO2. Research in biotechnology of microalgae including eukaryotic algae and cyanobacteria is an important and attractive topic which attracts the interests of the public widely. This Research Topic aims to create a collection approaching biotechnology and biology of eukaryotic algae and cyanobacteria. Basic science of molecular biology and biochemistry is indispensable for proceeding future application of microalgae, and hence, the title includes "molecular biology" and "biochemistry". Broad range of basic and applied science of microalgae is appreciated in this special topic.